2014
DOI: 10.3141/2408-10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Milling and Other Repairs on Smoothness of Overlays on Asphalt Pavements

Abstract: The application of asphalt overlays on existing pavements comprises a significant percentage of the maintenance activities undertaken to restore asphalt pavement condition. The improvement of surface smoothness from overlay construction is gaining increasing attention because smoother overlays are likely to have longer lives as a result of decreased dynamic loading and to provide fuel economy benefits and greater comfort to road users. This paper presents a study in which the California Department of Transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies in the field have analyzed the interaction between milling drum teeth and asphalt layers. The research papers [6][7][8][9][10][11][12][13] provide information and results focused, mainly, on the aspects related to how the dislocation of asphalt concrete components (mixture of aggregates and filler/bitumen in solid state) occurs under the action of the cutter teeth, while the specialized literature [14][15][16][17][18][19][20][21] investigates the effect of the milling process on the milling teeth. The experimental research [14] evaluated, through statistical analysis, the wear process of teeth from two different manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the field have analyzed the interaction between milling drum teeth and asphalt layers. The research papers [6][7][8][9][10][11][12][13] provide information and results focused, mainly, on the aspects related to how the dislocation of asphalt concrete components (mixture of aggregates and filler/bitumen in solid state) occurs under the action of the cutter teeth, while the specialized literature [14][15][16][17][18][19][20][21] investigates the effect of the milling process on the milling teeth. The experimental research [14] evaluated, through statistical analysis, the wear process of teeth from two different manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…us, this paper mainly focusses on the latter. Research studies have demonstrated that thicker overlay lead to lower roughness after rehabilitation and delayed the propagation of reflective cracking significantly but increased the rutting depth sometimes [16][17][18]. However, engineers often get stuck in choosing an appropriate milling and resurfacing thickness if field core tests were not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effect of milling and overlays on pavement roughness, although not specifically for thin overlays. Hung et al analyzed pavement condition survey data from the California Department of Transportation (Caltrans) and found that the IRI before overlay was the most significant predictor of overlay smoothness, as pavements with lower preoverlay IRIs were smoother than those with higher preoverlay IRIs ( 14 ). In addition, the effects of milling and digouts varied depending on the level of preoverlay IRI, with better results being obtained when the preoverlay IRI was greater than 120 in./mi.…”
mentioning
confidence: 99%